Dialogia dos corpos: trajetórias de corpos dançantes de jovens universitários amazônidas - (:unkn) unknown (Universidade Federal do Amazonas, 2021)
In the present study, I sought to understand through meaningful dancing experiences narratives from the Young university students how this activity inserts itself on the adversity facing process on their schooling trajectory. The theoretical foundation sustains itself on Bakhtin and Vigotski’s ideas interrelation, which have historical dialectical materialism as their theoretical reference and work methods. Dancing is, in this paper, understood through the historical-cultural psychology perspective, as the meaningful mediator on the individual’s constitution, to which permits understand the meaning of what I call “dancing bodies”, articulating the dance to resilience and emancipation processes. By becoming reflection’s object, this articulation directly converses with the individual’s constitution through their activity, identity and consciousness, checking how dance relates to one’s methods to overcoming adversity, given the many of them through one’s life trajectory. To that end, I used a multi-method methodology, with individual interviews (narrative and semi-structured). The analysis pointed out that dancing has transforming resources on the relational socialization and identity forming process of the youths. The affective-relational dimension characterised itself in this study as an important aspect to the “dancing bodies” weaving process. That’s what helped them being welcomed and cared for in different moment’s on the youth’s lives. The affection went through meanings that emerge on the subjectivity constitution and follows the movement to reorganize the behaviour of the subject assigning meaning to those emoticons. The study also revealed that the different segments of school education offered sometimes opportunities, sometimes through dance practices in particular, the entry point to higher education. It has also shown that the dancing body was affected by the Covid-19 Pandemic. However, the dance made itself present on the lives of the Youth as an instrument on the fight for existence and resilience. It echoed on the discourses that it materializes on the shaping of the dancing bodies and establishes connection with the new meanings throughout its development, allowing ressignification of the present experiences and propelling them to the future.
Keywords: Dança na arte; Dança na educação; CIENCIAS HUMANAS: PSICOLOGIA; CIENCIAS HUMANAS: EDUCACAO; Dança; Jovens; Universitários; Resistência